Karakteristik Bakteri Asam Laktat dari Dengke Naniura - Simanjuntak, Rosnawyta; Naibaho, Benika (Jurnal Riset Teknologi Pangan dan Hasil Pertanian (RETIPA), 2023)
Lactic acid bacteria involved in the food fermentation process generally take place spontaneously, especially in traditional Indonesian food processing. One of the local foods that is the traditional food of the people of Tapanuli, North Sumatra, is dengke naniura. This food is processed without cooking with fire only by giving utte (orange) jungga juice and spices left for a few hours. This study aims to obtain lactic acid bacteria isolates from dengke naniura. The first step of this research is to make dengke naniura; and followed by the isolation of lactic acid bacteria from dengke naniura using de Man Rogose and Sharpe media in order to obtain isolates of lactic acid bacteria with general characteristics; and characterization was carried out to determine the specific characteristics, of lactic acid bacteria isolates, which included the Gram stain test, motility test, catalase reaction test, shape, and ability to survive at various acids. The isolation results obtained as many as 10 isolates suspected of being lactic acid bacteria, as indicated by the presence of a clear zone around the isolates. The characterization of lactic acid bacteria showed that all isolates were Gram-positive, rod and spherical in shape, non-motile, and could grow at low acidity pH 3.0. The catalase test showed that eight isolates reacted negatively to catalase and two positively to catalase. Of the 10 isolates tested, as many as 8 showed characteristics of lactic acid bacteria.